Non‐Invasive Tumor‐Naïve Minimal Residual Disease Detection of Liver Cancer by Incorporating Circulating Tumor DNA Features and Alpha‐Fetoprotein: A Prospective Study - Qingqi Ren; Shiyong Li; Guolin Zhong; Yunfei Li; Dao‐Ling Huang; Liangliang Zhang; Yumin Feng; Guanghui Long; Mao Mao (Cancer Medicine)
ABSTRACT Background and Purpose Liver cancer has a high recurrence rate of 50%~70% for early‐stage patients. Minimal residual disease (MRD) is strongly linked to liver cancer early recurrence. Identifying MRD through reliable prognostic biomarkers, such as circulating tumor DNA (ctDNA), could significantly benefit these patients by enabling timely intervention and improved outcomes. Materials and Methods A prospective study enrolled 32 liver cancer patients undergoing radical surgery. Peripheral blood samples (8 mL) were collected before and after surgery. In this study, we expanded upon our previously developed multi‐omics assay, initially designed for liver cancer early detection by calculating a cancer signal score (PHCC), to determine the MRD status (named SeekInCure). This process integrated protein tumor marker alpha‐fetoprotein (AFP) and cancer genomic hallmarks, copy number aberration (CNA) and fragment size (FS). Results Of the enrolled patients, 78.1% were in early stages, and before surgery, 87.5% of patients had successfully detected the cancer signal in blood. After radical surgery, 23 patients were MRD‐negative, exhibiting better overall survival compared to the MRD‐positive patients (n = 9, p < 0.01). Patients maintaining undetectable cancer signals pre‐ and post‐surgery showed 100% survival, conversely, those keeping with detectable signals had a 55.6% mortality rate. Conclusion This prospective study highlights the prognostic value of ctDNA‐based tumor‐naïve MRD detection through a multi‐omics assay in early‐stage liver cancer patients.